2016
DOI: 10.2463/mrms.2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Crossover Comparison of Gadoxetic Acid Dose for Liver MRI in Normal Volunteers

Abstract: Purpose: We performed a quantitative intraindividual comparison of the performance of 0.025-and 0.05-mmol/kg doses for gadoxetic acid-enhanced liver magnetic resonance (MR) imaging.Materials and Methods: Eleven healthy volunteers underwent liver MR imaging twice, once with a 0.025-and once with a 0.05-mmol/kg dose of gadoxetic acid. MR spectroscopy and 3-dimensional gradient-echo T 1 -weighted images (3D-GRE) were obtained before and 3, 10, and 20 min after injection of the contrast medium to measure T 1 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…With regard to gender, Motosugi et al showed a predisposition towards male sex [29]. In contrast, Shah et al proposed a correlation between TSM and female sex [14].…”
Section: Potential Individual Risk Factorsmentioning
confidence: 99%
“…With regard to gender, Motosugi et al showed a predisposition towards male sex [29]. In contrast, Shah et al proposed a correlation between TSM and female sex [14].…”
Section: Potential Individual Risk Factorsmentioning
confidence: 99%
“…29,30 Further, the dramatic changes in T 1W after the administration of contrast will also impact PDFF estimates by LFA strategies. [31][32][33] To examine the residual bias in LFA-CSE-MRI over a wide range of T 1 values, a computer simulation was performed. Noiseless SGRE signals were generated using Equation 4 with T 1W = 380, 586, 680 and 830 ms to predict the effects of T 1W variation on PDFF estimation with LFA-CSE-MRI, using LFA acquisition parameters experiment described below for the in vivo liver study.…”
Section: Bias In Lfa-cse-mri Resulting From T 1w Variationmentioning
confidence: 99%
“… T 1W values from 380–800 ms have been reported . Further, the dramatic changes in T 1W after the administration of contrast will also impact PDFF estimates by LFA strategies …”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that higher doses of gadoxetic acid improves the quality of arterial phase dynamic contrast-enhanced MRI [28–30]. Based on these data, the local standard of care at our institution is to administer 0.05 mmol/kg gadoxetic acid.…”
Section: Discussionmentioning
confidence: 99%